Determination of Nutrient Accumulation Pattern of New Aromatic Rice (Oryza sativa L.) as Influenced by Different Applied Fertilizers and Plant Spacing (The Agriculturists, 2020)
Field and laboratory experiments were conducted at the Bangabandhu Sheikh MujiburRahman Agricultural University, Gazipur, during boro season of 2015-2016 to determine the response of rice crop (BU Dhan 2) to different plant densities under different fertilizer levels. The variety was grown with three fertilizer levels viz. recommended (57-10-8-7-0.9 kg NPKSZn ha-1), 50% higher (114-20- 16-14-1.8 kg NPKSZn ha-1) and 50% lower (28.5-5-4-3.5-0.45 kg NPKSZn ha-1) than recommended level and three plant spacing (20 cm x 25 cm, 20 cm x 20 cm and 20 cm x 15 cm) representing wider, standard and closer plant densities. Nutrient uptake of the variety was higher at higher level of fertilizer and closer plant spacing. The highest grain yield 5.18 t ha-1 of the variety was associated with the highest nutrient uptake under higher dose of fertilizer at closer plant spacing. This treatment combination also showed the highest nitrogen (86.53 kg ha-1), phosphorus (9.85 kg ha-1), potassium (103.9 kg ha-1), sulphur (12.27 kg ha-1) and zinc uptake (265.76 g ha-1) of the variety, although nutrient use efficiency was higher at lower fertilizer level under wider plant density.The Agriculturists 2020; 18(1) 31-41